Respuesta :

Answer:

(1, 0, 2)

Step-by-step explanation:

[3   -1  2 | 7  ]

|6 -10  3 | 12|

[1   -1   4 |  9 ]

To the first row, add -3 times the values of the third row

To the second row, add -6 times the values of the third row

[0   2  -10 | -20 ]

|0  -4  -21 | -42 |

[1    -1    4 |  9   ]

To the second row, add 2 times the values in the first row

[0   2  -10 | -20 ]

|0  0  -41  | -82 |

[1    -1    4 |  9   ]

z =  -82 / -41

z = 2

2y - 10(2) = -20

y = 0

x - 0 + 4(2) = 9

x = 1

ACCESS MORE